Relationship of Body Mass Index (BMI) and Sex in Adolescent Training Resistance - Tyas Sari Ratna (Gaster, 2021)
Â Adolescents 18-21 years of age today have problems related to movement that result in changes to resistance training. Exercise resistance is expressed in VO2max. Body mass index and gender are factors that influence VO2max. The purpose of this study is to analyze the relationship between body mass index and sex on VO2Max and to analyze how closely the relationship is. The type of this study is an observational study with a purposive sampling technique with a point time approach design with a total of 183 samples with criteria for healthy samples aged 18- 21 years. The independent variable in this study was exercise endurance (VO2max), and the dependent variable was body mass index and gender. The data is processed using software for data analysis. From the data normality test using Kolmogorov Smirnov for Body Mass Index data with a value of 0.001, sex data with a value of 0.000, VO2Max data with a value of 0.000 which indicates abnormal data. Test Data analysis using the Spearman rank test resulted in the value of gender and VO2max 0.001 with r value of 0.203 and body mass index value and VO2max -0.015 with r value of 0.766.There is a correlation between body mass index and sex on VO2Max.